A STUDY OF ENGINEERING STUDENT’S ABILITY IN UNDERSTANDING PARTS OF SPEECH AT STTIND PADANG - Allen Christy Jufri; Asis Warni (Journal of Social and Economics Research, 2023)
The purpose of this study is to see the student’s understanding in identifying and classifying parts of speech at English Subject. Parts of speech are English basic component in which words are recognized and classified based on their lexical functions. They consist of eight major parts of speech, such as nouns, pronouns, verbs, adjectives, adverbs, conjunctions, prepositions and interjections. The instrument of this study is written test, there are two kinds of test: first, Identifying the italic word in a sentence and second is classifying the words that consist of 30 words about parts of speech then the participants sort them and classify into the table. The participants of this study are 40 students that consist of four majors; mining engineering, industry engineering, environmental engineering and information system students. From each major the researcher took 10 students. Based on the results of the research, it can be stated that the students’ understanding of parts of speech are varied on the range of 40%-90%. The lowest is ability to understand adverb, only 40% or 16 students ably to identify it, the highest one is Interjection, 90% or abou 36 students easily point out it.